Use of Different Levels of High Fiber Sunflower Meal in Commercial Leghorn Type Layer Diets - Rezaei, M.; Hafezian, H. (International Journal of Poultry Science, 2007)
An experiment was conduced to evaluate the inclusion of high fiber Sunflower Meal (SFM) in commercial layer diets in a completely randomized design with 4 treatments, 8 replicates and 4 hens in each replicate. After determining chemical composition of sunflower meal 4 diets with equal CP (14.5%) and other nutrients except energy containing 0, 5, 10, 15 percent of high fiber sunflower meal were formulated. During the experiment feed consumption, hen-day egg production, egg weight, feed conversion ratio, haugh unit, egg specific gravity and mortality, were measured weekly. In the beginning and the end of the experiment body weight of the hens were measured individually. The results indicated that use of 10 percent of sunflower meal hadn`t significant effect on feed consumption, hen-day egg production. However increasing sunflower meal up to 15 percent decreased feed consumption, egg production and egg weight, 5.70, 7.06 and 5.49 percent respectively, while feed conversion ratio increased significantly (p